Another new species of karst-associated pitviper (Serpentes, Viperidae: Trimeresurus) from the Isthmus of Kra, Peninsular Thailand - Idiiatullina, Sabira S.; Pawangkhanant, Parinya; Suwannapoom, Chatmongkon; Tawan, Tanapong; Chanhome, Lawan; Nguyen, Tan Van; David, Patrick; Vogel, Gernot; Poyarkov, Nikolay A. (European Journal of Taxonomy, 2024)
We describe a new species of karst-dwelling pitviper from Chumphon Province of Peninsular Thailand, in the Isthmus of Kra, based on morphological and molecular data (2427 bp from cyt b, ND4 and 16S rRNA mitochondrial DNA genes). Morphologically, Trimeresurus kraensis sp. nov. is distinguished from other congeners by the following combination of morphological characters: a dark/bottle-green dorsum with reddish-brown or purple crossbands; pale green venter lacking dark dots; stripes present on the lateral sides of the ventrals; internasals generally in contact; one large supraocular scale on each side of the head; iris pale copper; tail brown with dark purplish-brown crossbars; dorsal scales in 21–21–15 rows; ventral scales 167 in a single male, 169–171 in females; subcaudal scales 62 in a single male, 52–54 in females, all paired. White vertebral spots present in males, located on approximately every two or four dorsal scales; dark brown spots forming discontinuous pattern present on 1–3 lateral dorsal scale rows; males with reddish-brown postocular stripe with jagged edges. The new species differs from the morphologically similar species Trimeresurus venustus s. str. by a notable divergence in cytochrome b mitochondrial DNA gene sequences (p = 5.9%).